Prevalence and Associated Factors of Low-Level Viremia in Chronic Hepatitis B Patients After Long-Term Therapy with Nucleos(t)ide Analogs - Han, Jiajia; Guo, Yifei; Zhang, Xueyun; Zhang, Yao; Sun, Jian; He, Jingjing; Mao, Richeng; Huang, Yuxian; Zhang, Jiming (Turkish Journal of Gastroenterology, 2023)
Background: Low-level viremia is usually defined as a detectable but lower than 2000 IU/mL hepatitis B virus DNA level after 12 months or longer duration of antiviral therapy in chronic hepatitis B patients. In this study, we aimed to clarify the factors associated with lowlevel viremia in patients during long-term monotherapy with tenofovir disoproxil fumarate or entecavir.Methods: Chronic hepatitis B patients having received entecavir or tenofovir disoproxil fumarate treatment for 12 months or more were enrolled from October 2019 to October 2021 at a tertiary hospital in Shanghai, China. In accordance with their hepatitis B virus DNA levels, chronic hepatitis B patients were grouped into 3 categories, hepatitis B virus DNA > 2000 IU/mL, low-level viremia, and complete virological response (hepatitis B virus DNA < 10 IU/mL). Compared with complete virological response patients, factors related to lowlevel viremia were evaluated.Results: This study enrolled a total of 160 chronic hepatitis B patients, whose duration of treatment ranged from 12 to 144 months. In total, 107 patients achieved complete virological response, 51 showed low-level viremia, and 2 showed hepatitis B virus DNA > 2000 IU/mL. After multivariate logistic regression analysis, hepatitis e antigen-positivity (odds ratio = 6.479, 95% CI: 2.480-16.922, P = .000), entecavir treatment (odds ratio = 4.742, 95% CI: 1.855-12.118, P = .001), and duration of therapy (odds ratio = 0.168, 95% CI: 0.072-0.388, P = .000) were independently associated with low-level viremia.Conclusion: Having received long-term antiviral treatment, low-level viremia still occurred in 31.9% of patients. Longer duration of therapy was a protective factor, and HBeAg-positivity and entecavir treatment were risk factors for low-level viremia.Cite this article as: Han J, Guo Y, Zhang X, et al. Prevalence and associated factors of low-level viremia in chronic hepatitis B patients after long-term therapy with nucleos(t)ide analogs. Turk J Gastroenterol. 2023; 34(1): 53-61.